Clinical and epidemiological features of Turkish children with 2009 pandemic influenza A (H1N1) infection: Experience from multiple tertiary paediatric centres in Turkey - (:unkn) unknown (INFORMA HEALTHCARE, 2011)
Background: In April 2009 a novel strain of human influenza A, identified as H1N1 virus, rapidly spread worldwide, and in early June 2009 the World Health Organization raised the pandemic alert level to phase 6. Herein we present the largest series of children who were hospitalized due to pandemic H1N1 infection in Turkey. Methods: We conducted a retrospective multicentre analysis of case records involving children hospitalized with influenza-like illness, in whom 2009 H1N1 influenza was diagnosed by reverse-transcriptase polymerase chain reaction assay, at 17 different tertiary hospitals. Results: A total of 821 children with 2009 pandemic H1N1 were hospitalized. The majority of admitted children (56.9%) were younger than 5 y of age. Three hundred and seventy-six children (45.8%) had 1 or more pre-existing conditions. Respiratory complications including wheezing, pneumonia, pneumothorax, pneumomediastinum, and hypoxemia were seen in 272 (33.2%) children. Ninety of the patients (11.0%) were admitted or transferred to the paediatric intensive care units (PICU) and 52 (6.3%) received mechanical ventilation. Thirty-five children (4.3%) died. The mortality rate did not differ between age groups. Of the patients who died, 25.7% were healthy before the H1N1 virus infection. However, the death rate was significantly higher in patients with malignancy, chronic neurological disease, immunosuppressive therapy, at least 1 pre-existing condition, and respiratory complications. The most common causes of mortality were pneumonia and sepsis. Conclusions: In Turkey, 2009 H1N1 infection caused high mortality and PICU admission due to severe respiratory illness and complications, especially in children with an underlying condition.
Keywords: Children; influenza A; H1N1; mortality; MORTALITY; UK